Concentrations and sources apportionment of polycyclic aromatic hydrocarbons in 1 sediments from the 2 Uganda side of Lake Victoria - Kerebba, Nasifu; Ssebugere, Patrick; Kwetegyeka, Justus; Arinaitwe, Kenneth; Wasswa, John (Environmental Science: Processes & Impacts, 2017)
This paper presents the levels and possible sources of selected polycyclic aromatic hydrocarbons (PAHs) in surface sediments from Napoleon Gulf and Murchison Bay of Lake Victoria. Sediment samples were extracted and cleaned up for PAHs using UNEP, 1992 and EPA method 3630C protocols, respectively. The analysis of sample extracts was done using a gas chromatograph coupled to a mass spectrometer. Fifteen congeners, mostly the high molecular weight PAHs (HPAHs) (4-6 rings) were detected. Total (Σ) concentrations varied from 44.2 to 80.2 ng g-1 dry weight (d.w.) at Napoleon Gulf while those at the Murchison Bay ranged from 17.0 to 55.0 ng g-1 d.w. Statistical analysis showed no significant difference in the concentrations of PAHs among sites (p <0.05, ANOVA). It was noted that the concentrations for most sampling sites were far below the lowest effect levels based on the Sediment Quality Guidelines except for one station at the Napoleon Gulf. Principal component analysis and diagonistic ratios indicated that PAHs of combustion and petroleum origin were dominant and brought mainly by atmospheric deposition.